Design considerations for combining augmented reality with intelligent tutors. (December 2018) - Herbert, Bradley; Ens, Barrett; Weerasinghe, Amali; Billinghurst, Mark; Wigley, Grant
Highlights: The effectiveness of Intelligent Tutoring Systems in psychomotor domains can potentially be enhanced by combining them with Augmented Reality paradigms. Due to ITS complexity and design, work on the use of ITSs with AR is significantly limited and how these paradigms work together is not well understood. Existing work shows that combining ITSs with AR enhances significantly enhances performance and learning. Combining AR with ITS requires a gateway interface and networking capabilities in both the ITS and the AR application, due to non-standardised mechanisms used in these systems. Additional research on the design of the interface; authoring systems for ITSs in AR and their learning effectiveness is required. Graphical abstract: Abstract: Augmented Reality overlays virtual objects on the real world in real-time and has the potential to enhance education, however, few AR training systems provide personalised learning support. Combining AR with intelligent tutoring systems has the potential to improve training outcomes by providing personalised learner support, such as feedback on the AR environment. This paper reviews the current state of AR training systems combined with ITSs and proposes a series of requirements for combining the two paradigms. In addition, this paper identifies a growing need to provide more research in the context of design and implementation of adaptive augmented reality tutors (ARATs). These include possibilities of evaluating the user interfaces of ARAT and potential domains where an ARAT might be considered effective.